Three-dimensional flow and turbulence structure in electrostatic precipitator by stereo PIV - Ullum, T; Larsen, PS; Özcan, O (SPRINGER, 2004)
Stereo PIV was employed to study the three-dimensional velocity and turbulence fields in a laboratory model of a negative corona, barbed-wire, smooth-plate electrostatic precipitator. The calculated electric drift velocity of charged seeding particles is subtracted from the measured particle velocity to obtain the gas velocity. Results show how the strength of the secondary flow (in the form of longitudinal rolls) and the level of turbulence (as well as its degree of anisotropy) increase with increasing axial position, increasing current density, and decreasing bulk velocity. Both of these features of the gas flow are crucial to the performance of precipitators.
Keywords: CORONA; Engineering; Mechanics